Keterikatan Kerja: Keadilan Distributif Keadilan Prosedural dan Keadilan Interpersonal di Mediasi oleh Kepuasan Kerja Pada Pegawai Dinas Kesehatan Kabupaten Solok - Novalinda, Novalinda; Elfiswandi, Elfiswandi; Veri , Jhon (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to find out how much work attachment: distributive justice, procedural justice and interpersonal justice are mediated by job satisfaction in employees of the Solok Regency Health Office. The type of researcher used is quantitative. The data analysis used is Structur Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. By distributing a questionnaire of 82 respondents. The results of the data analysis concluded that there was an influence There was no significant influence of Distributive Justice on Job Satisfaction, There was a significant influence of Procedural Justice on Job Satisfaction, There was no significant influence of Interpersonal Justice on Job Satisfaction, There was a significant influence of Distributive Justice on Job Engagement, There was an insignificant influence of Procedural Justice on Engagement, There was no significant influence of Interpersonal Justice on Job Engagement, There was a significant influence of Job Satisfaction on Job Engagement, Job Satisfaction did not mediate Distributive Justice on Job Engagement, Job Satisfaction did not mediate Procedural Justice on Engagement, Job Satisfaction did not mediate Interpersonal Justice on Job Engagement